The role of European age-group championships in senior participation rates - Hanley, B. (2016)
A study of the value of the European U20 and U23 Championships in maintaining participation in athletics for life is very important from the point of view of athletes, coaches, administrators and those interested in physical activity programmes. The aim of this study was to evaluate the role of the European Athletics U20 and U23 Championships in maintaining participation in athletes who had high performances at junior level. The objectives involved in achieving this aim were: to analyse the overall participation rates across the 10 years of each athlete post-junior competition; to analyse participation rates in the end five years of this period to examine specifically the value of the U23 championships; to compare different track and field events; and to compare results between different EAA member federations.